Response of Sulphur and Zinc on The Growth and Yield Traits of Sesame (Sesamum indicum L.) At Old Himalayan Piedmont Plain Soil - Mohammad Sohidul Islam; Mohamed Tawane Ali; M. Kamrul Hasan; Abdikasim Hashi Wais; ASM Golam HAFEEZ; M. Kaium Chowdhury (ISPEC Journal of Agricultural Sciences)
A field experiment was carried at the Agronomy Research Field, Hajee Mohammad Danesh Science and Technology University, Dinajpur, Bangladesh to find out the effect of sulphur and zinc on the growth and yield traits of sesame. The experiment consisted two factorial naming Factor A: Three levels of sulphur as 0 (S1), 18 (S2) and 24 (S3) (0, 100, 150 kg gypsum/ha), and Factor B: Three levels of zinc as 0 (Zn1), 1.44 (Zn2) and 2.88 (Zn3) (0, 4.0, 8.0kg zinc sulphate/ha). The total treatment combinations were i) T1 (S1Zn1), ii) T2 (S1Zn2), iii) T3 (S1Zn3), iv) T4 (S2Zn1), v) T5 (S2Zn2), vi) T6 (S2Zn3), vii) T7 (S3Zn1), viii) T8 (S3Zn2), ix) T9 (S3Zn3). The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Seasame cv. BARITil 4 was used as test crop. The experimental results revealed that sulphur (18 kg ha-1) + zinc (1.44 kg ha-1) (S2Zn2) applications greatly increased the leaf, petiole, stem and root at different days after sowing. Higher dry weight of different parts and yield traits i.e. no of capsules and capsules weight were produced by the application of sulphur (18 kg ha-1) + zinc (1.44 kg ha-1) among all treatment combinations at different growth stage.